Monetary Policy and Inflation Control in Nepal: An Empirical Assessment - Shrestha, Jamuna; Adhikari, Gyan Mani; Lamichhane, Sushil; Parajuli, Devendra (International Research Journal of MMC, 2025)
This paper examines the impact of monetary policy in regulating inflation in Nepal through a time series analysis covering 1989-2024. The analysis uses the annual data on inflations rate, growth of money supply, interest rates, fluctuations in the exchange rate, growth in Gross Domestic Product (GDP) and the openness of trade to analyze both short-run and long-run relationships between monetary policy tools and inflation. The data were gathered in the secondary sources and mainly the annual reports of Nepal Rastra Bank, economic bulletins as well as the publications of world bank and international monetary fund. The study concludes that monetary policy has played a moderate role in dealing with inflation in Nepal using the Autoregressive Distributed Lag (ARDL) bounds testing strategy and a Vector Error Correction Model (VECM) that produces the error-correction coefficient of -0.385 indicating the rate of adjustment to the long-run equilibrium. The increase in money supply has a positive and statistically significant correlation with inflation hence validating the monetarist school of thought, but interest rates show a negative though insignificant effect on inflation. Changes in exchange rates turn out to be an influential factor of inflation in terms of import-price effects. The error-correction system implies that about 38.5 per cent of short-term disequilibrium is eliminated every year. Here, the results indicate that although conventional monetary policy instruments have some effectiveness, structures and exogenous shocks still have significant roles in the inflation processes in Nepal. The research will be useful in helping the policymakers, central bankers, and researchers to formulate more effective policies in the control of inflation within Nepal economy.